Nilai-Nilai Pendidikan Akhlak Adat Jamau Kutai - Anggi Sri Bintang; Ngadri Yusro; Nurjannah Nurjannah; Eka Yanuarti (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
This study aims to determine the traditions of the Jamau Kutai and the values of moral education contained in the traditions of Jamau Kutai. This research is field research with a qualitative approach. Data collection techniques used in this study include observation, interviews, and documentation. The results of this study indicate that the custom of Jamau Kutai is a customary event that contains such as reading the Qur'an, speeches, religious lectures, reading prayers, and eating dishes. while the values of moral education contained in the traditional Jamau Kutai, namely moral education include the growth of a culture of mutual help, cooperation, loyalty to friends. The conclusion from the results of this study is that the Jamau Kutai tradition already contains very strong religious values while the values of moral education contained in the Jamau Kutai custom are to foster a culture of mutual help, cooperation, and loyalty to friends. Keywords: Adat, Jamau Kutai, Moral Education